Realising Inclusive Human Resource Management: The Role of Organizational Culture and Gender in Enhancing Well-Being and Reducing Stress - Ratnawati, Shinta; Widayanti, Ipuk; Ashari Nur, Sofyan (Universitas Brawijaya, Indonesia, 2025)
Employee psychological well-being and stress management are becoming increasingly pressing issues in the challenging modern world of work. This study analyzes the relationship between organizational culture, social support, and gender on psychological well-being and employee stress. This study used explanatory quantitative research with a cross-sectional approach. The population of this study was professionals working in Indonesia, and a purposive sampling technique was used. A total of 172 respondents who met the criteria were included in this study. Data collection was conducted using an online questionnaire measured on a Likert scale. Data analysis used Structural Equation Modeling (SEM) with the help of Smart PLS software. The results showed that an inclusive organizational culture and social support significantly improve psychological well-being and reduce employee stress levels. Meanwhile, gender roles do not moderate the relationship between organizational culture and social support on psychological well-being, but gender moderates the relationship between organizational culture and stress levels. This study implies the importance of creating an inclusive organizational culture and providing adequate social support to improve well-being and reduce employee stress in the workplace.